Report Submitted to W. K. Kellogg Foundation on the Second Year of Operation of the Grant to Demostrate the Significant Contribution that Rural Young People can Make to Rural Development in Latin America - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
This document has parts in english and spanish.